“How Do We Replace Concrete?” : Building Sector Professionals Addressing Knowledge Asymmetries about Climate-wise Housing - Koskela, Merja; Kääntä, Liisa; Salmela, Eveliina; Syrjälä, Henna (HERMES - Journal of Language and Communication in Business, 2025)
The aim of the article is to explore how housing and construction field experts give advice concerning climate-wise housing in a professional magazine, and what types of potential knowledge asymmetries are connected with the advice. By potential knowledge asymmetries we refer to situations in which experts writing to other experts in a professional magazine indicate differences in the depth, scope, or type of knowledge possessed about a topic by offering advice to the readers. By offering advice, the authors position themselves as having epistemic authority on the topics they address. Based on argumentative, editorial-type texts in a Finnish building and construction field magazine, a pragmatic discourse analysis combined with qualitative content analysis of ways of advice-giving and sources of potential knowledge asymmetries in the context of climate-wise housing was conducted. The findings reveal that (1) all combinations of explicit-implicit and targeted-not-targeted advice-giving are present in the data, but explicit and not-targeted advice are most prevalent; (2) there are five main sources of potential knowledge asymmetries concerning system-level phenomena: technical, legal-regulatory, political, economic, and expertise-related. The paper concludes by discussing the potential and limitations of advice-giving in written expert-to-expert contexts in contributing to advancing climate-wise housing.